IMPLEMENTASI ASESMEN DAN EVALUASI PEMBELAJARAN MATEMATIKA BERBASIS DIGITAL MELALUI INTEGRASI INTERACTIVE FLAT PANEL (IFP) DAN POLYPAD DI SEKOLAH DASAR - Lilik Noeraini; Barokah Isdaryanti; Wiwi Isnaeni (STKIP Subang, 2026)
The development of digital technology has driven a transformation in the assessment and evaluation system for learning in elementary schools. The Independent Curriculum positions assessment as an integral part of the learning process, serving to continuously monitor student progress. This study aims to describe the implementation of digital-based mathematics learning assessment and evaluation through the use of Interactive Flat Panels (IFP) and Polypads at SDN 1 Sambongrejo. The study used a qualitative descriptive approach with data sources consisting of teachers, students, and learning documents. Data collection techniques included observation, interviews, documentation, and analysis of learning tools. The study results indicate that the use of IFPs and Polypads supports the implementation of diagnostic, formative, and summative assessments in a more interactive, authentic, and student-centered manner. In addition to improving the quality of learning feedback, the use of digital technology also helps teachers evaluate learning outcomes more effectively. These findings suggest that digital technology integration can be an alternative innovation in mathematics learning assessment and evaluation in elementary schools.